Regulating Labour : The State, Neo-Conservatism and Industrial Relations - Shields, John, 1954-; McBride, Stephen; Haiven, Larry (Book collections on Project MUSE., 1990)
Have Mulroney, Reagan and Thatcher beaten labour into the ground? Are unions a spent force? Do ordinary people in Canada, the United States and Great Britain truly believe in the so-called free market? How are the Swedish social democrats handling challenges to their consensus society? Is there indeed a neo-conservative hegemony for the nineteen-nineties? These are some of the questions which the authors of this sixth Socialist Studies Annual try to answer. They present case studies from various countries, using the social and political insights of Gramsci and other progressive thinkers.